2012
DOI: 10.21608/ejar.2012.161889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Irradiation Combined With B.T.BIOCIDE Treatments on Some Insect Pests in Laboratory

Abstract: The study was done in the laboratories of Bollworms, Leafworm and piercing & sucking Research Departments of Plant Protection Research Institute during 2010. The tested pests and the biocide, Protecto were exposed to gamma irradiation doses at National Center for Radiation Research and Technology, Egypt. Three tested insects were tested includes: pink bollworm, Pectinophora gossypiella (Saund.) newly hatched and fourth instar larvae, cotton leafworm, Spodoptera littoralis (Boisd.) 4 th instar larvae and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
1
0
0
1
Order By: Relevance
“…Given the above data and considering the desire to develop environmentally promising approach, simulations treatment of IST and Bta could be used as a novel protocol for control lepidopteran pests effectively. The noteworthy difference in the toxicity of Bta combined with gamma radiation doses comparing with individual treatment in the present study goes in line with (AMER et al 2012) who found that the gamma radiation doses 150, 250, 350 reduced the LC 50 of Bt. Moreover, (Sayed and El-Helaly 2018) found that the low doses 40 and 60 Gy were highly effective on the Sex ratio was more declined at the favor of male at most simultaneous treatments than either control or individual treatments.…”
Section: Discussionsupporting
confidence: 90%
“…Given the above data and considering the desire to develop environmentally promising approach, simulations treatment of IST and Bta could be used as a novel protocol for control lepidopteran pests effectively. The noteworthy difference in the toxicity of Bta combined with gamma radiation doses comparing with individual treatment in the present study goes in line with (AMER et al 2012) who found that the gamma radiation doses 150, 250, 350 reduced the LC 50 of Bt. Moreover, (Sayed and El-Helaly 2018) found that the low doses 40 and 60 Gy were highly effective on the Sex ratio was more declined at the favor of male at most simultaneous treatments than either control or individual treatments.…”
Section: Discussionsupporting
confidence: 90%
“…Perlakuan dengan dosis generik 100 Gy mampu menyebabkan terhambatnya reproduksi imago kutudaun (Hallman 2011). Dosis letal untuk perlakuan iradiasi sinar gamma [ 60 C0] terhadap Aphis craccivora Koch (Hemiptera: Aphididae) adalah 150 Gy (Amer et al 2012).…”
Section: Pendahuluanunclassified